The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/11038128.2012.758777
|View full text |Cite
|
Sign up to set email alerts
|

Computer use in educational activities by students with ADHD

Abstract: Aim: The aim of this study was to investigate computer use in educational activities by students with attention deficit hyperactivity disorder (ADHD) in comparison with that of students with physical disabilities and students from the general population. Methods: The design of the study was cross-sectional with group comparison. Students with ADHD (n=102) were pair-matched in terms of age and sex with students with physical disabilities and students from the general population (n=940) were used as a reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Data were not available concerning medication and co-morbidity. Details of recruitment and response rate for adolescents with ADHD in this project have been previously published by Bolic, Lidström, Thelin, Kjellberg, and Hemmingsson (2013). Analysis of response bias regarding age and sex has been reported earlier (Bolic, Lidström, Thelin, Kjellberg, & Hemmingsson, 2013), and demonstrated no significant differences between the participants in the present study and non-respondents (p>0.05).…”
Section: Participantsmentioning
confidence: 63%
See 2 more Smart Citations
“…Data were not available concerning medication and co-morbidity. Details of recruitment and response rate for adolescents with ADHD in this project have been previously published by Bolic, Lidström, Thelin, Kjellberg, and Hemmingsson (2013). Analysis of response bias regarding age and sex has been reported earlier (Bolic, Lidström, Thelin, Kjellberg, & Hemmingsson, 2013), and demonstrated no significant differences between the participants in the present study and non-respondents (p>0.05).…”
Section: Participantsmentioning
confidence: 63%
“…Results on ICT use by adolescents with physical disabilities at school and during leisure, and ICT use by adolescents with ADHD at school have been published elsewhere (Bolic, Lidström, Thelin, Kjellberg, & Hemmingsson, 2013;Lidstöm, 2011;Lidström, Ahlsten, & Hemmingsson, 2010;Lidström, Granlund, & Hemmingsson, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pijl and co-workers (2014), describes support as important for maintaining motivation and interest in school, and consequently not dropping out from school. It could also be one explanation as to why previous research show that students in need of special educational support often experience restricted participation in educational activities at school (Bolic, Lidström, Thelin, Kjellberg, & Hemmingsson, 2013;Eriksson, Welander, & Granlund, 2007;Ferguson, 2008;Lidström, Granlund, & Hemmingsson, 2012;Raggi & Chronis, 2006;Trampush et al, 2009). The result of the study, that many students had not received the adjustments and support they perceived they needed should be taken seriously, since research also have shown that students in need of special educational support are largely overlooked (Pijl et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…In this final section different issues and implications are gathered to enlightening important perspectives and implications uncovered throughout the review. Bolic et al (2013) investigates access to and satisfaction with the use of technologies among students with ADHD. The students with ADHD wish to use computers more often and for more educational activities but indicate that schools are more prepared to meet the needs of students with physical disabilities than those with ADHD.…”
Section: Technology Based Interventions For Group Work and Collaborationmentioning
confidence: 99%